Organic amines as templates: pore imprints with exactly matching sizes in a series of metal–organic frameworks. Issue 80 (5th September 2018) - Zhao, Nian; Yang, Lun; Xie, Bo; Han, Juanjuan; Pan, Qiyun; Li, Xiang; Liu, Meifeng; Wang, Yu; Wang, Xiuzhang; Zhu, Guangshan
Abstract : Three metal–organic frameworks have been synthesized with an amine template strategy whose pore sizes exactly matched those of templates. Abstract : Three kinds of organic amines have been used as soft templates for constructing a series of metal–organic frameworks with variable pores. The pore sizes of these MOFs exactly matched those of amines, confirming the template effect of these amines.